Synthesis, characterization, spectral studies and antifungal activity of Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II) complexes with 3,3′-bis[N,N,di(carboxymethyl)-aminomethyl]-o-cresol sulphonphthalein - Pandey G.; Narang K.K. (My University, 2025)
Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II) complexes of the type Na4[ML(H2O)2] of the ligand, 3,3′-bis[N,N-di(carboxymethyl)-aminomethyl]-o-cresol sulphonphthalein (Xylenol Orange, Na4H2L), have been synthesized and characterized by different physico-chemical (elemental analyses, solubility, electrolytic conductances, magnetic susceptibility measurements) and spectral (u.v.-vis, i.r., e.s.r., and powder X-ray diffraction) techniques for their structure determination. The data suggest 1:1 (M:L) compositions and octahedral geometries around M(II) except for Cu(II). Antifungal activity of the complexes measured against ten fungi show significant activity against Alternaria brassicicola, Alternaria solanai, Cercospora species and Helminthosporium oryzae and moderate antifungal activity against Curvularia species, Curvularia lunata, Curvularia penniseti, Colletotrichum capsici, Aspergillus niger, Aspergillus flavus Erysiphae pisi and Fusarium udum fungi. © 2006 Taylor & Francis.